A comparison of US and Norwegian regulation of coumarin in tobacco products. Issue 4 (5th December 2003) - Givel, M
Abstract : Objective: This paper examines policy processes regarding why the USA and Norway have not regulated coumarin in tobacco. Design: A qualitative analysis of all tobacco industry documents regarding coumarin since the 1950s from the 1998 US Master Settlement Agreement and subsequent legal settlements. Additional data were collected from newspaper reports, general internet search engines, journal articles, scholarly reports, court cases, statutes, regulations, and informal correspondence with tobacco control experts in Norway. Main outcome measure: An overview, summary, and analysis of all documents related to coumarin. Results: In the USA from 1954 until 1985 when coumarin was reportedly removed from domestic cigarettes, but not from pipe tobacco until 1996, and not at all from imported Indian bidi cigarettes, regulatory efforts were stymied. In Norway, from 1973 to the present, the tobacco industry has never disclosed whether its tobacco products contain coumarin. In both the USA and Norway, the extreme delay and lack of vigorous evidence gathering and significant remedies were caused by tobacco industry assertions that revealing tobacco additives was a violation of trade secrets, and by weak regulatory authority and efforts to regulate coumarin. Conclusion: Vigorous and expeditious regulatory investigations and remedies for harmful additives in tobacco, such as coumarin, can protect the public health. Astute insider and outsider political advocacy by health advocates is required to hold elected officials and civil servants publicly accountable for failing to enact disclosure laws and to engage in effective regulatory efforts.